Design, optimization and fabrication of an integrated optoelectronic sensing chip with applications in groundwater contaminant detection and biosensing - Erickson, Timothy, author; Lear, Kevin L., advisor; Roberts, Jacob, committee member; Notaros, Branislav, committee member; Collins, George, committee member (Colorado State University. Libraries, 2014)
The LEAC (Local Evanescent Array Coupled) chip is a CMOS-compatible, waveguide-based, label-free, optoelectronic sensor, which can function as a biosensor or environmental sensor. Unique among optoelectronic sensors, the ~1 cm2 LEAC chip features an integrated photodetector array, which increases device portability, enables multi-analyte detection on a single waveguide, and simplifies system instrumentation. At its core, the LEAC chip is simply a precision refractometer, which can sense very small changes in refractive index (~5x10-6) in its multiple upper cladding sensing regions. The chip can be functionalized for detection of biomarkers or groundwater contaminants, which bind or diffuse into the waveguide's upper cladding sensing region, thereby producing a measurable change in refractive index. The research conducted during my doctoral studies has addressed two important goals. The first was to optimize the chip's sensing performance. The second goal was to run proof of concept experiments, in order to demonstrate its utility in practical sensing applications. By incorporating multiple engineering improvements, the sensing performance of the LEAC chip has been improved to the point where it may be competitive with low-end surface plasmon resonance (SPR) systems for bulk refractive index sensing. We have demonstrated the LEAC sensing platform for both environmental and biosensing applications. These include sensing aromatic hydrocarbons such as benzene, toluene and xylenes in groundwater at sub-ppm concentrations and detection of the cardiac infarction biomarker TroponinI. Research results have been communicated in peer-reviewed journals and presented at conferences, as summarized in Appendix J. Additionally, the intellectual property that was developed during the course of research activities has served as the basis for several patent filings. This dissertation provides a comprehensive account of research conducted on the LEAC sensing platform, while working as a graduate student in Dr. Kevin Lear's laboratory. It is structured in the following manner. In Chapter 1, the basic functionality of LEAC chip is introduced, while providing the necessary background to motivate its development. Chapter 2 provides a comprehensive and comparative overview of other label-free biosensors and groundwater aromatic hydrocarbon contaminant sensors. It reviews the requirements of other sensing systems and demonstrates the uniquely portable aspects of LEAC chip technology. It is provided for completeness, in order to summarize the state-of-the-art in the field of portable sensing and highlight some of the unique advantages of the LEAC sensor. In Chapter 3, the engineering aspects of performance optimization over prior art are described in detail. Whereas the 1st generation LEAC chip was fabricated at Avago Technologies, all 2nd generation LEAC chips have been fabricated by myself in the CSU cleanroom or at the Colorado Nanofabrication Lab in Boulder. The development of 2nd generation LEAC chips, including device physics, modeling, and fabrication is rigorously described. In Chapter 4, the bulk refractive index sensing capabilities of the chip are demonstrated as well as the chip's capacity to perform multi-analyte dry sensing assays . Through design improvements, it is quantitatively shown that the 2nd generation chip is over two orders of magnitude more sensitive than the 1st generation chip. In Chapter 5, the environmental sensing capabilities of the LEAC chip are presented. Teflon AF is first characterized as a unique film for sensing BTX (benzene, toluene, and xylene) contaminants in water using near-IR surface plasmon resonance. Then LEAC chips functionalized with Teflon AF are demonstrated for BTX sensing in water at sub-ppm concentrations. Interference from potential matrix interfering contaminants is evaluated. In Chapter 6, the biosensing capabilities of the LEAC chip are discussed. The LEAC chip is validated for detection of Troponin I. In Chapter 7, areas for future improvements to the LEAC sensing platform are briefly touched upon along with concluding remarks. A number of appendices related to very specific technical aspects of my work have been included as helpful documentation. These appendices include fabrication process flows, the data acquisition system, transimpedance amplifier design, grating coupler designs, mask designs (including testing structures), and other protocols. A list of publications and conferences is provided at the end of this report in Appendix I.
Keywords: biosensor; groundwater sensor; integrated photodetector; optical waveguide; BTEX; environmental contaminant sensor